2015
DOI: 10.1186/1747-597x-10-3
|View full text |Cite
|
Sign up to set email alerts
|

The SALOME study: recruitment experiences in a clinical trial offering injectable diacetylmorphine and hydromorphone for opioid dependency

Abstract: BackgroundThe Study to Assess Long-term Opioid Medication Effectiveness (SALOME) is a two-stage phase III, single site (Vancouver, Canada), randomized, double blind controlled trial designed to test if hydromorphone is as effective as diacetylmorphine for the treatment of long-term illicit opioid injection. Recruiting participants for clinical trials continues to be a challenge in medical and addiction research, with many studies not being able to reach the planned sample size in a timely manner. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
(23 reference statements)
0
23
0
Order By: Relevance
“…For example, participants reported that study enrolment was deterred by the burden and conditions of involvement ; concerns about confidentiality ; mistrust of researchers ; and reluctance to be a treatment ‘guinea pig’ . In contrast, recruitment was encouraged by access to study information ; the presence of medical care and monitoring ; treatments being desirable ; and reimbursements or incentives .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, participants reported that study enrolment was deterred by the burden and conditions of involvement ; concerns about confidentiality ; mistrust of researchers ; and reluctance to be a treatment ‘guinea pig’ . In contrast, recruitment was encouraged by access to study information ; the presence of medical care and monitoring ; treatments being desirable ; and reimbursements or incentives .…”
Section: Discussionmentioning
confidence: 99%
“…Responding to these problems, addiction researchers have already identified strategies that can be incorporated into their RCT designs to facilitate and enhance recruitment. These include offering financial reimbursements or incentives ; providing non‐monetary incentives, such as coffee or bus tokens ; increasing the odds of receiving the experimental treatment ; simplifying the study referral processes ; providing treatments which appeal to the target population or are otherwise unavailable ; sending appointment reminders ; inviting trial participants to recruit others from their social networks ; highlighting the potential benefits of the study to patients and staff ; and engaging with peer and community organizations to secure their commitment to the research .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Despite this, medically prescribed DAM is not available in Canada without special access due to regulatory and political reasons . In the quest to find a more politically acceptable alternative to DAM, the Study to Assess Long‐term Opioid Maintenance Effectiveness (SALOME) trial was conducted to test if injectable hydromorphone (HDM) was non‐inferior to injectable DAM as a second‐line treatment for severe opioid use disorder . HDM is currently licensed for moderate to severe pain treatment but at smaller doses than utilized in the SALOME trial for treatment of opiate dependence.…”
Section: Introductionmentioning
confidence: 99%